Effect of the Tea Tree Oil on Growth Performance, Meat Quality, Serum Biochemical Indices, and Antioxidant Capacity in Finishing Pigs - Yang, Tianyu; Feng, Feifei; Zhan, Kang; Ma, Xiaoyu; Jiang, Maocheng; Datsomor, Osmond; Zhu, Xinyu; Huo, Yongjiu; Zhao, Guoqi (Frontiers in Veterinary Science, 2022)
The increased use of antibiotics continues to pose a threat to public health because of the increasing concern of antibiotic residue. Tea tree oil (TTO) is an extract of the Australian plant Melaleuca alternifolia with anti-inflammatory and antioxidant properties. However, there is little information on TTO supplementation in the diet of finishing pigs. Hence, the present study aimed to investigate the effect of TTO supplemented diets on the growth performance, meat quality, serum biochemical indices, and antioxidant capacity of the finishing pigs. Our results showed that TTO supplementation increased (P < 0.05) the mRNA expression of insulin-like growth factors -I (IGFs-I), growth acceleration hormone (GH), and heart fatty acid-binding protein (H-FABP), while the mRNA expression of myostatin gene (MSTN), and calpain-1 (CAST) decreased by the TTO supplementation, compared with the control group. In addition, TTO supplementation increased (P < 0.05) serum alkaline phosphatase (ALP), immunoglobulin G (IgG), and IgM levels but decreased (P < 0.05) serum aspartate transaminase (AST) concentration, relative to the control group. In addition, we found that the live weight and intramuscular fat enhanced (P < 0.05) significantly, and muscle pH 24 min value, cooking loss, and shear force decreased (P < 0.05) dramatically in the TTO group. The TTO supplementation increased (P < 0.05) C18:2n6t concentration and decreased (P < 0.05) C12:0 and C16:0 concentration, relative to the control group. Dietary supplementation with TTO decreased (P < 0.05) malondialdehyde (MDA) and increased (P < 0.05) glutathione peroxidase (GSH-Px) activity in serum. These results indicated that TTO supplementation could improve immunity and antioxidant, carcass traits, the nutritional value of pork, and the antioxidant capacity of finishing pigs. Therefore, TTO has potential positive effects as a feed additive in the pig industry.